The Influence of Al-Qur'an Learning Methods “Ummi” on the Ability to Read the Qur'an: A Quantitative Study - Hadi Muhaini; Afifah Afifah; Noor Insani Maulidiya (International Journal of Islamic Thought and Humanities, 2023)
Everyone definitely wants to have a happy life both in this world and in the hereafter, therefore education is the path that must be taken to achieve all of this, while the Koran is a guide to make it easier to walk the path traversed. The purpose of the study entitled the effect of the Ummi Method on the ability to read the Koran for fourth grade students MI Muhammadiyah 27 Surabaya in the 2022-2023 school year is to find out the ability to read the Koran for fourth grade students MI Muhammadiyah 27 Surabaya in the 2022-2023 academic year, and to know whether there is or whether or not the influence of the Ummi Method has on the ability to read the Koran for fourth grade students MI Muhammadiyah 27 Surabaya in 2022-2023. This research is a quantitative study with data collection techniques using observation, documentation, and questionnaires. The results of this study show that the Ummi Method in class IV MI Muhammadiyah 27 Surabaya in 2022-2023 is classified as very good with a percentage of 87%, and the ability to read the Koran for class IV MI Muhammadiyah 27 Surabaya in 2022-2023 is classified as very good with a percentage of 79%, while The effect of the Ummi Method on the ability to read the Koran for class IV MI Muhammadiyah 27 Surabaya students in 2022-2023 is shown by the results of the Chi Square calculation of 18.022 which is greater than the significant level of 3.841. Keywords: Ummi method, ability to read the Koran.